Analisis Praksis Pengangkatan Wali Hakim dalam Fikih Munakahat Madzhab Syafi’i dan Hukum Positif - Eka; Amrullah, Muhammad Ikhsan (El 'Ailaah, 2025)
Marriage n the view of slam and the state s a sacred bond that s the foundation of the formation of the family and society. One of the mportant elements n the marriage contract s the existence of a marriage guardian, whose validity s a condition for the validity of marriage according to the majority of scholars and the state. However, n practice, t s not uncommon for cases where the guardian of the nasab s unknown, reluctant to marry without sharia reasons, or s unable to carry out his function, so the role of the guardian judge as a replacement s needed. This study aims to examine and compare the provisions for the appointment of guardian judges according to the fiqh munakahat madzhab Shafi'i and positive law. Using qualitative methods and literature review research types, this study examines the legal basics, procedures, and principles used n each legal system. The results of the study show that the two have similarities n terms of the urgency of guardian judges to maintain the validity of marriage and protect women's rights. However, there s a fundamental difference n the mechanism of mplementation: Shafi'i jurisprudence tends to be normative, and flexible, while positive law emphasizes formal procedures through state nstitutions. This study concludes that these different approaches need to be harmonized n practice so as not to cause legal doubts and to ensure protection for all parties n the mplementation of the marriage contract.